The Influence of Self-Regulation, Emotional and Spiritual Intelligence on Islamic Religious Education Learning Outcomes of Junior High School Students in Terara District - Baiq Yulfa Khairani; Yusuf (EDUJAVARE: International Journal of Educational Research, 2026)
Students' Islamic Religious Education (PAI) learning outcomes show variations in achievement that are not only influenced by cognitive factors, but also by internal factors within the students. Self-regulation, emotional intelligence, and spiritual intelligence are thought to play an important role in supporting the success of the PAI learning process. This study aims to analyze the influence of self-regulation, emotional intelligence, and spiritual intelligence on the Islamic Religious Education (PAI) learning outcomes of Junior High School (SMP) students in Terara District. This study uses a quantitative method. The study population includes all junior high school students in Terara District. The research sample was determined from four schools, namely SMP Negeri 1 Terara, SMP Negeri 2 Terara, SMP Al Badriyah, and SMP IT Al Hasaniyah, with a total of 50 students as respondents. Data collection was carried out through distributing questionnaires to measure self-regulation, emotional intelligence, and spiritual intelligence. PAI learning outcome data were obtained from student report card scores. Data analysis used t-test to determine the partial effect of each independent variable and F-test to test the simultaneous effect on the dependent variable. The results of the study showed that self-regulation, emotional intelligence, and spiritual intelligence had a significant partial effect on Islamic Religious Education (PAI) learning outcomes. Simultaneously, these three variables were also proven to have a significant effect on the Islamic Religious Education (PAI) learning outcomes of junior high school students in Terara District. The findings of this study indicate that improving Islamic Religious Education (PAI) learning outcomes needs to be supported by strengthening the ability of self-regulation, emotional management, and internalization of spiritual values. The results of this study can be a basis for schools and teachers in designing more holistic Islamic Religious Education (PAI) learning strategies.